The structure of molecules : An introduction to molecular spectroscopy - Barrow, Gordon M. (The general chemistry monograph series, 1963)
Radiation and the energies of molecules - Rotational spectra and the size and sape of molecules - Vibrational spectra and the flexibility of molecules - The simultaneous rotation and vibration of diatomic molecules - Spectra due to change in the arrangement of the electrons of a molecule - The emission or dissipation of energy by excited molecules.